Effects of Three Organic Spices (Ginger, Clove, and Turmeric) on the Proximate and Sensory Properties of Tomato Powder - Achimugu, Solomon; Rudin, Nur Ahmad; Usman, G. O. (Proceeding International Conference on Science and Engineering, 2021)
Abstract. In this study, the effects of three organic spices (ginger, clove and turmeric) on the proximate and sensory properties of tomato powder evaluated revealed that moisture, ash, crude fiber, fat, protein and carbohydrate content ranged from 15.89 - 18.60%, 5.50 - 7.41%, 5.32 - 7.41%, 4.10 - 4.59%, 11.40 - 14.65% and 51.33 - 52.47% respectively. The increase in the proportion of organic spices decreased the moisture content and protein content while increasing significantly the ash and carbohydrate content of the samples. However, the fat content of the control and sample DDD were significantly different (P?0.05). The increase in the ash content of the supplemented samples could be attributed to the minerals and phytochemical abundance in organic spices. Generally, consumer’s preference decreased with increase in the proportion of organic spices. This could be because the products are novel to most people.